Developing Self-Regulation and Digital Learning to Improve Students' Critical Reasoning in Economics - Rizkyna Amalia; Indri Murniawaty (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
Critical thinking is a crucial skill required in 21st-century learning, particularly in economics. Students are expected to analyze problems, analyze information, and make informed choices. Many students still demonstrate inadequate levels of critical thinking due to limited self-control during learning, inefficient use of digital learning resources, and an unsupportive learning environment. Previous studies have generally examined these elements individually, yet research examining the combined impact of self-regulation, YouTube teaching resources, and the learning environment on students' critical reasoning in economics is limited. Therefore, this study seeks to examine the partial and overall impact of self-regulation, YouTube usage, and the learning environment on students' critical thinking skills in economics. This study employed a quantitative method with an exploratory research design. The population comprised all eleventh-grade students of SMA Negeri 1 Tengaran, while the sample was drawn through proportional random sampling. Data were collected through questionnaires using a Likert scale instrument. Before processing the data, the measurement tools were tested for validity and reliability. The collected data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis to determine the relationships between variables. Research shows that self-regulation during learning, YouTube usage, and the learning environment, both partially and simultaneously, have a positive impact on students' critical thinking skills in economics. Therefore, educators and institutions are encouraged to design creative learning tactics that encourage independent learning, maximize the use of digital resources, and foster a cooperative and reflective learning environment to enhance students' critical thinking skills.